Electoral Law Innovation to Strengthen Women's Representation in Parliament - Virdaus, Saivol; Musofiana, Ida (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
In a healthy democratic system, it is important to involve women and men in policy-making and decision-making processes to achieve balance and justice. In Indonesia, despite the requirement for 30% female candidates for parliamentary positions, the representation of women elected remains below this target. This study uses a juridical-normative method with conceptual, legislative, and comparative approaches to answer how to ensure at least 30% female representation in parliament. The findings show that the current electoral system affects the low level of female election success, especially with the plurality voting system that presents significant challenges for women. Currently, Indonesia implements a gender quota as a candidate quota, which only mandates the nomination of 30% of women. However, its implementation has been ineffective as women still struggle to be elected, particularly under the open proportional system. To ensure at least 30% female representation, Indonesia needs to consider adopting a gender quota system like the reserved seat model, as applied in Rwanda, which allocates 30% of parliamentary seats for women, or in Uganda, where seats are specifically allocated for women in each district, thus increasing the chances for women to be elected.